Association between serum vitamin D and severe headache or migraine: A population-based analysis - Shunfa Hao; Renyi Qian; Yiru Chen; Jingfang Liu; Xiaoyan Xu; Yunxiang Guan (PLoS ONE, 2025)
Background Vitamin D is thought to play a role in the development of migraine, but the nature of the relationship is still not fully understood. Although some studies have shown an association between vitamin D deficiency and migraine, other studies have had inconsistent or inconclusive results. Therefore, further research is needed to better understand the relationship between vitamin D and migraine headaches. Methods We selected 9142 participants from the 2001–2004 National Health and Nutrition Examination Survey (NHANES). In our study, the term "serum vitamin D" refers to the concentration of 25OHD2 + 25OHD3 (nmol/L) in the blood. Migraine was assessed based on self-reports in the miscellaneous pain section of the NHANES questionnaire. Associations between vitamin D and the risk of migraine were examined using multiple logistic regression, smoothed curve fitting, and stratified analyses. Results In our study, 20.53% of the participants suffered from migraine. The prevalence of migraine was higher in those with lower serum vitamin D levels. Participants in the highest quartile of serum vitamin D levels were found to have a 16% lower prevalence than those in the lowest quartile in the fully adjusted model (OR = 0.84, 95% CI 0.71–0.99). This result was supported by stratified analysis and smoothed curve fitting. Conclusion Our study showed a significant negative correlation between serum vitamin D levels and the prevalence of migraine in American adults.